Risk factors of lower respiratory tract infection caused by Stenotrophomonas maltophilia: Systematic review and meta-analysis - Wang, Yiwei; Wang, Yizhi; Rong, Hechen; Guo, Zhonghong; Xu, Jie; Huang, Xiaoping (Frontiers in Public Health, 2023)
Objective: To systematically evaluate the risk factors of lower respiratory tract infection caused by Stenotrophomonas maltophilia for better clinical treatment. Methods: PubMed, Embase, the Cochrane Library, Web of Science, China Journal full-text Database (CNKI), Wanfang Database (WanFang Data), VIP (VIP), and China Biomedical Literature Database (CBM) were selected and published by June 2022 about the risk factors of lower respiratory tract infection of S. maltophilia. Two researchers independently screened the literature, extracted data, and quality evaluation according to the inclusion and exclusion criteria. RevMan 5.4 software was used for Meta-analysis. Results: A total of 18 articles were included, including 10 in English and 8 in Chinese. Meta analysis showed that the risk factors of lower respiratory tract infection caused by S. maltophilia included disease severity, hospitalization days, use of glucocorticoids, invasive procedures, use of broad-spectrum antibiotics and use of more than 3 Antibiotics. The OR values of patients with hospitalization, mechanical ventilation, use of more than 3 Antibiotics, endotracheal intubation and tracheotomy were the highest. Specific hospitalization days (OR=14.56, 95% CI:6.12~23.01), mechanical ventilation (OR=14.16, 95% CI:5.85~34.3), use of more than 3 Antibiotics (OR=6.21, 95% CI:1.24~31.14), tracheal intubation (OR=6.07, 95% CI:1.97~3.64), tracheotomy (OR=3.77, 95% CI:1.09~13.04). Conclusion: There are many risk factors for lower respiratory tract infection of S. maltophilia, which can occur in patients with severe illness, high APACHE-II score, invasive procedures, and the need for broad-spectrum antibiotics.In terms of the host, these patients are characterized by impaired immune function, severe illness and long-term hospitalization, which objectively leads to the infection of Stenotrophomonas maltophilia.Therefore, strengthening the monitoring, prevention and control of patients with risk factors of Stenotrophomonas maltophilia infection is conducive to reducing the risk of infection and death.